Alton's Paradox Foreign Film Workers and the Emergence of Industrial Cinema in Latin America. - Poppe, Nicolas (SUNY Press, 2021)
Uses extensive archival research to explore the manifold contributions of foreign film workers to emerging film industries in Latin America from the 1930s to early 1940s.